Impact of the time of returning soil fertility in the fallow land of Arfak Tribe in West Papua - Heru Joko Budirianto; Insar Damopolii (Jurnal Biologi Tropis, 2022)
The Papuan people turn their unproductive land into fallow land. The length of the fallow period needs to be studied to identify its effect on the fertility status of the former plantation land. This study aimed to identify the fertility of the former Arfak tribal gardens based on different fallow periods. This research was conducted in Ayambori Village (two types of land, namely Active Gardens (AK) and ten-year-old fallow land (Br1)), and Bremi (three types of land, namely former cocoa plantations (Br2), primary forest (Br3), and coastal fallow land (Br4)) Manokwari Regency, West Papua Province. Soil samples were taken in each ex-garden land using a soil drill with a depth of 0-20 cm. Soil analysis was carried out at Laboratory. The elements analyzed included pH, Organic C, total N, C/N ratio, available P2O5, potential P2O5, potential K2O, Ca, Mg, K, Na, CEC, KB, Fraction, and soil texture class. The results showed that Br1, Br2, and Br3 fields showed moderate fertility status. On the other hand, AK1 and Br4 fields showed low fertility status. The research concluded that land age did not affect soil fertility status. Soil texture impacts soil fertility, where clay is better than sandy. Further research can examine the influence of microbes on soil fertility in fallow land.